The AMP-Activated Protein Kinase KIN10 Is Involved in the Regulation of Autophagy in Arabidopsis - Chen, Liang; Su, Ze-Zhuo; Huang, Li; Xia, Fan-Nv; Qi, Hua; Xie, Li-Juan; Xiao, Shi; Chen, Qin-Fang (Frontiers in Plant Science, 2017)
Autophagy is a highly conserved system in eukaryotes for the bulk degradation and recycling of intracellular components. Autophagy is involved in many physiological processes including development, senescence, and responses to abiotic and biotic stress. The adenosine 5’-monophosphate (AMP)-activated protein kinase AMPK positively regulates autophagy in mammals; however, the potential function of AMPK in plant autophagy remains largely unknown. Here, we identified KIN10, a plant ortholog of the mammalian AMPK, as a positive regulator of plant autophagy and showed that it acts by affecting the phosphorylation of ATG1 (AUTOPHAGY-RELATED GENE 1) proteins in Arabidopsis. Transgenic Arabidopsis lines overexpressing KIN10 (KIN10-OE) showed delays in leaf senescence, and increased tolerance to nutrient starvation, these phenotypes required a functional autophagy pathway. Consistent with KIN10 having a potential role in autophagy, the nutrient starvation-induced formation of autophagosomes and cleavage of GFP-ATG8e were accelerated in the KIN10-OE lines compared to the wild type. Moreover, the KIN10-OE lines were less sensitive to drought and hypoxia treatments, compared with wild type. Carbon starvation enhanced the level of phosphorylated YFP-ATG1a in the KIN10-OE lines compared to that of wild type. Together, these findings suggest that KIN10 is involved in positive regulation of autophagy, possibly by affecting the phosphorylation of ATG1s in Arabidopsis.